2022
DOI: 10.54097/hset.v11i.1386
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lovastatin and its Lipid-lowering and Anti-Cancer Effects

Abstract: Lovastatin is traditionally used to reduce the amount of cholesterol and lipid levels in many diseases, but its anti-cancer properties are now discovered. By regulating and modulating crucial signaling small G-proteins of cancer cell including Rho, Rac, and Ras, lovastatin can alter cancer cell division, migration, and induce cell death. Lovastatin has a similar structure to HMG-CoA and thus can competitively bind to HMG-CoA reductase (HMGR) and work as a hypolipidemic medicine. The anti-cancer effect of lovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Statins are a class of drugs that inhibit HMG-CoA reductase, resulting in reduced cholesterol production [ 129 ]. In the 1970s, the statins were first discovered by Dr. Akira Endo, the Japanese microbiologist, in the filamentous fungi Penicillium (P.) citrinum and later in A. terreus ; lovastatin was first discovered in 1978 by Alberts, Chen, and others, and for a long time, fungi were the only source for the statins [ 129 , 138 ]. The United States Food and Drug Administration approved the first statin, lovastatin, as anti-hypercholesterolemic drug in August 1987 [ 129 ].…”
Section: Biological Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins are a class of drugs that inhibit HMG-CoA reductase, resulting in reduced cholesterol production [ 129 ]. In the 1970s, the statins were first discovered by Dr. Akira Endo, the Japanese microbiologist, in the filamentous fungi Penicillium (P.) citrinum and later in A. terreus ; lovastatin was first discovered in 1978 by Alberts, Chen, and others, and for a long time, fungi were the only source for the statins [ 129 , 138 ]. The United States Food and Drug Administration approved the first statin, lovastatin, as anti-hypercholesterolemic drug in August 1987 [ 129 ].…”
Section: Biological Investigationmentioning
confidence: 99%
“…The structure of chemically synthesized statins, such as atorvastatin, rosuvastatin, fluvastatin, and cerivastatin, differs from natural statins; nonetheless, there is a similitude to natural statins in the HMG CoA-like inhibitory moiety [ 129 ]. Lovastatin (290) has long been used to lower cholesterol and lipid levels in several diseases, it is well-known for decreasing cholesterol and increasing the hepatic uptake of LDL-C via upregulating low-density lipoprotein receptors (LDLR) and because it has a structure similar to HMG-CoA, it can bind competitively to HMG-CoA reductase (HMGR) and act as a hypolipidemic medication [ 138 ]. Leach et al reported that a Lipoprotein-associated phospholipase A2 (Lp-PLA2) inhibitor decreased the growth of atherosclerotic plaque in the Watanabe heritable hyperlipidemic (WHHL) rabbit study.…”
Section: Biological Investigationmentioning
confidence: 99%